A Scoping Review of Strategic Approaches to Enhance Maternal Health and Antenatal Care Services in Coastal Areas - Wahyuningsih, Windu Syawalina; Rajagukguk, Vivi Rosalin; Laro, Maria Natalia (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Globally, maternal mortality remains a major public health concern, with an estimated 223 maternal deaths per 100,000 live births and more than 800 women dying every day from preventable pregnancy-related causes. The burden is disproportionately high in low-resource settings, including coastal and island regions. This review aimed to identify the strategic approaches implemented to improve maternal health and antenatal care in these areas.Methods: A systematic search was conducted for studies published from 2000 to April 2025 in the PubMed, Scopus, and ScienceDirect databases. Of the 1,054 articles identified, 1,017 were screened, 54 met the eligibility criteria for full assessment, and 41 studies were ultimately included in the review.Results: The findings revealed several key strategies: mobile clinics, outreach services, and emergency transportation for pregnant women (n=6); telemedicine and mHealth initiatives (n=12); engagement of community health workers and local personnel (n=13); strengthening maternal waiting homes, delivery systems, and referral mechanisms; and integration of ANC with other health programs (n=10). These approaches highlight efforts to overcome socioeconomic, geographic, and cultural barriers to accessing essential maternal health services in coastal regionsConclusion: We recommend empowering local health workers, leveraging technology for outreach, strengthening referral and transport systems using data for targeted actions, and fostering community engagement to improve maternal health outcomes in coastal regions. Understanding the effectiveness and challenges of these strategies is crucial for developing context-specific interventions to reduce maternal mortality and enhance ANC coverage in underserved coastal communities.